2011
DOI: 10.1111/j.1365-2516.2010.02441.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Optivate®, a new high purity concentrate of factor VIII with von Willebrand factor, in patients undergoing surgery

Abstract: The efficacy and safety of Optivate(®) was assessed in 23 surgical operations, orthopaedic (12) including 5 revision arthroplasties, ophthalmic (1), ENT (1), dental (6), liver biopsy (2), and removal of portacath (1) on 15 teenagers and adults with severe haemophilia A. The preoperative dose was calculated to raise the FVIII concentration to 100 IU dL(-1). Subsequent doses were targeted to maintain at least 50 IU dL(-1). There were 11 major and 12 minor operations categorized as receiving intensive replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Types and brands of factor concentrates administered in the selected studies are shown in Table 1. Forty‐five studies [20–64] reported patients with HA receiving FVIII concentrates (Table 2), 15 studies [65–79] patients with HB treated with FIX concentrates (Table 3) and 11 studies [80–90] VWD patients treated with VWF containing products (Table 4). Owing to the peculiar pathophysiologic situation, six studies [91–96] reporting haemophilia patients who had central venous access devices (CVAD) in order to facilitate long‐term regular concentrate administration (prophylaxis, immune tolerance induction) were analyzed separately (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Types and brands of factor concentrates administered in the selected studies are shown in Table 1. Forty‐five studies [20–64] reported patients with HA receiving FVIII concentrates (Table 2), 15 studies [65–79] patients with HB treated with FIX concentrates (Table 3) and 11 studies [80–90] VWD patients treated with VWF containing products (Table 4). Owing to the peculiar pathophysiologic situation, six studies [91–96] reporting haemophilia patients who had central venous access devices (CVAD) in order to facilitate long‐term regular concentrate administration (prophylaxis, immune tolerance induction) were analyzed separately (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [32,41,63,73,75] reported only treatment of bleeding episodes (three in HA, two HB), whereas in most cases patients on regular prophylaxis (17 studies; 16 HA, 1 VWD) or undergoing surgical procedures (11 studies; 4 HA, 3 HB, 4 VWD) or both (24 studies; 15 HA, 7 HB, 2 VWD) were also evaluated. Twelve studies [39,48,53,57,64,65,69,71,83,84,86,90] reported only surgical interventions (6 HA, 2 HB, 4 VWD), three of these studies (2 HA, 1 HB) focusing on factor administration by continuous infusion (CI) [39,53,71]. Patients with HA and inhibitors receiving FVIII concentrates for immune tolerance induction were also included in three studies [34,38,47], whereas indications of treatments were not specified in two (one HA, one HB) [20,70].…”
Section: Study Patient and Treatment Characteristicsmentioning
confidence: 99%
“…Overall Optivate was well tolerated. There have been no reports of inhibitor development to FVIII and/or VWF with Optivate in this study or any of the other clinical studies [2,[6][7][8][9] or from postmarketing experience to date.…”
mentioning
confidence: 93%
“…Optivate is licensed in several countries worldwide for the treatment of Haemophilia A in both adults and children [6][7][8][9]. This letter reviews data from a BPL sponsored single centre, randomized pharmacokinetic (PK) study comparing Optivate and Haemate P (also known as Humate P) in VWD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation